Professionalization Experiences of Newely Employed Nurses in Clinical Settings in Iran - H Seif; Z Parsa Yekta; A Nikbakht Nasrabadi; N Rasoolzadeh (Tehran University of Medical Sciences, 2005)
Background & Aim: Nursing professionalization is a developmental experience that evolves throughout professional nurses' careers. Nursing systems that prepare nurses include experiences that are important in the early development of nursing identity. This phenomenenon is also foundational to the assumption of various nursing roles. Methods & Materials: A phenomenological approach was used in order to explore the meanings of professionalization experiences among participants. Data were gathered through series of semi structured interviews. Benner's interpretive method was used for data analysis. Results: From 17 famale and male beginner nurses who worked in different educational and private hospitals in Tehran points of view 5 main themes and 4 subthemes emerged which encompasses the whole experiences of participants' professioalization experiences. These themes included sufficient knowledge, well practical experiences and autonomy in practice to provide a comprehensive care. Conclusion: Faculty understanding of beginning nurses' definitions and experiences of nursing professionalization can provide insights that can be used to develop educational experiences that support and enhance students' professional nursing identity and ultimately affect their future practice. Faculty can also use knowledge of nurses' definitions of professionalization to enrich student learning.